2016
DOI: 10.1111/jnc.13415
|View full text |Cite
|
Sign up to set email alerts
|

MMP‐9 in translation: from molecule to brain physiology, pathology, and therapy

Abstract: Matrix metalloproteinase-9 (MMP-9) is a member of the metzincin family of mostly extracellularly operating proteases. Despite the fact that all of these enzymes might be target promiscuous, with largely overlapping catalogs of potential substrates, MMP-9 has recently emerged as a major and apparently unique player in brain physiology and pathology. The specificity of MMP-9 may arise from its very local and time-restricted actions, even when released in the brain from cells of various types, including neurons, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
272
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 310 publications
(281 citation statements)
references
References 302 publications
(608 reference statements)
7
272
0
2
Order By: Relevance
“…The b3 subunit is physically coupled to AMPARs via their cytoplasmic domains (Pozo et al, 2012) and is required for activitydependent synaptic scaling of glutamatergic synapses . For more information on the ECM, MMPs, and tissue inhibitors of MMPs, see Seals and Courtneidge (2003), Brew and Nagase (2010) Scofield et al (2015), Smith et al (2015a,b), and Vafadari et al, (2015).…”
Section: Extracellular Matrixmentioning
confidence: 99%
“…The b3 subunit is physically coupled to AMPARs via their cytoplasmic domains (Pozo et al, 2012) and is required for activitydependent synaptic scaling of glutamatergic synapses . For more information on the ECM, MMPs, and tissue inhibitors of MMPs, see Seals and Courtneidge (2003), Brew and Nagase (2010) Scofield et al (2015), Smith et al (2015a,b), and Vafadari et al, (2015).…”
Section: Extracellular Matrixmentioning
confidence: 99%
“…The interesting clinical data in this report demonstrating that a known gain-of-function single nucleotide polymorphism in the MMP9 gene is associated with increased motivation to consume alcohol despite negative consequences adds to literature encouraging examination of MMP-9 as a pharmacotherapeutic target for addiction. Previously, increased serum MMP-9 expression has been demonstrated in both alcohol-dependent and heroin-dependent patients (5). Outside of drug addiction, either serum MMP-9 levels or the C-1562T polymorphism have been correlated with a number of disorders, most notably mild cognitive impairment, Alzheimer’s disease, major depressive disorder, and fragile X syndrome.…”
mentioning
confidence: 99%
“…Thus, by virtue of its remodeling activity in the extracellular matrix, MMP-9 is uniquely situated to affect many diverse signaling pathways relevant to drug addiction. While MMP-9 is well established as both necessary and sufficient for long-term potentiation at hippocampal synapses, very little is known about its role in other brain sites, including the CeA (5). Previously, Michaluk et al (6) showed that rats that over-express an autoactive form of MMP-9 have greater numbers of long, thin spines, with no change in mushroom- or stubby-type spines in the hippocampus.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, recently, there are many evidences by many different studies shows that TIMP-1 is a kind of multifunctional protein. In addition of inhibiting MMP activity, it also has the unique function to stimulate tumor, participating in the process of cell apoptosis, cell proliferation and tumor angiogenesis etc., which has explained the mechanism to hint the poor prognosis in the breast cancer with its increased content (27). In addition of inhibiting MMP hydrolytic activity, it also has the unique cytokine-like function, capable of participating in the proliferation, apoptosis of tumor cell and tumor angiogenesis through signal transduction pathway (28).…”
Section: Discussionmentioning
confidence: 99%